Pugs and kisses - Howard, J. J. (Scholastic Inc., 2018)
Ana Ramos finds her own birthday lost in the excited preparation of her older sister's quinceanera. But she finds a bright spot in her new friend Calvin who she meets at the dog park while she's helping care for an elderly neighbor's dog. Calvin assumes the dog is her own, and she doesn't bother correcting him. But as their friendship grows and heads toward something more, she finds that her unintended lie is growing right along with their relationship.